Designing an IoT based stabilizer for home appliances - Ahmed, Hasnain; Jahan, Tanvir; Adittya, Tareq Islam; Sadique, Sadman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.